(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2022)
Proverbs, proverbial phrases and dialogisms, among other paremiological elements, can become communicative structures with great difficulties in contrastive work between two languages due to their particular characteristics. The aim of this study is to highlight the importance of identifying a series of strategies or theoretical guidelines that propose useful lines of action for the adaptation of sententious sentences during the translation process and in language learning. To be able to identify correspondences in other languages as well as to help, especially in the translation process, several theories, which were published in the digital magazine in translation, El trujamán, hosted by the Centro Virtual Cervantes, have been recovered and analysed in this paper. The authors Julia Sevilla Muñoz and Manuel Sevilla Muñoz developed several very useful theories for working with paremias.